Development of anti-immunocomplex specific antibodies and non-competitive time-resolved fluorescence immunoassay for the detection of estradiol - Leivo J.; Kivimäki L.; Juntunen E.; Pettersson K.; Lamminmäki U. (Springer Verlag, 2022)
Detection of circulatory estradiol has widespread use in various clinical applications. Particularly, the use of estradiol-specific antibodies in immunoassays is routinely used, mainly due to the cost efficiency and simplicity of the sample handling process. However, the circulatory levels of estradiol can be extremely low in some conditions, and beyond the current detection limit of existing competitive immunoassays. We describe the generation of anti-immunocomplex specific antibodies derived from synthetic antibody repertoire and the development of high-performance non-competitive immunoassay for the detection of estradiol. Phage display selections were used to isolate new antibodies from synthetic antibody library with the use of existing estradiol specific Fab fragment. The found antibodies were consecutively used to set up a time-resolved fluorescence-based immunoassay (TRFIA), which can be used to detect estradiol with exceptional sensitivity and specificity. The limit of detection and EC50 were shown to be 3.0 pg mL−1 and 32.4 pg mL−1 respectively.